A Double-Blind, Placebo-Controlled, Phase 3b Study of ATX-101 for Reduction of Mild or Extreme Submental Fat. Issue 12 (December 2019) - Glogau, Richard G.; Glaser, Dee Anna; Callender, Valerie D.; Yoelin, Steve; Dover, Jeffrey S.; Green, Jeremy B.; Breshears, Laura; Bowen, Beta
Abstract : BACKGROUND: ATX-101 (deoxycholic acid injection) is approved for reduction of moderate or severe submental fat (SMF). OBJECTIVE: To evaluate the efficacy and safety of ATX-101 in subjects with mild or extreme SMF. PATIENTS AND METHODS: Adults with mild or extreme SMF (based on clinician assessment) were randomized to receive ⩽6 treatments with ATX-101 or placebo. Efficacy end points, evaluated at 12 weeks after last treatment, included percentage of subjects who achieved ≥1-grade improvement in SMF from baseline based on both clinician and patient assessment (composite CR-1/PR-1 response) as well as multiple subject-reported outcomes. Safety end points included change in skin laxity and incidence of adverse events. RESULTS: Overall, 61.3% of ATX-101–treated subjects versus 6.7% of placebo-treated subjects with mild SMF and 89.3% versus 13.3% of subjects, respectively, with extreme SMF achieved a composite CR-1/PR-1 response ( p < .001 for both). ATX-101–treated subjects also reported higher levels of satisfaction and greater reductions in the psychological impact of SMF versus placebo-treated subjects regardless of baseline SMF severity. Skin laxity was unchanged or improved in most of the subjects. Adverse events were mainly mild/moderate, transient, and associated with the injection site. CONCLUSION: ATX-101 was efficacious and well tolerated for reduction of mild or extreme SMF.